2021
DOI: 10.1111/bjso.12500
|View full text |Cite
|
Sign up to set email alerts
|

Objectification limits authenticity: Exploring the relations between objectification, perceived authenticity, and subjective well‐being

Abstract: Five studies (total valid N = 834) examined whether objectification (i.e., being treated as a tool or an object to achieve others’ goals) reduces people’s perceived authenticity and subjective well‐being. Participants who experienced more objectification (Studies 1a and 1b), imagined being objectified (Study 2), or recalled a past objectification experience (Study 3) felt less authentic and reported lower levels of subjective well‐being than their counterparts. Moreover, perceived authenticity mediated the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 90 publications
1
13
0
1
Order By: Relevance
“…On the other hand, more people acting as ‘objectifiers’ means more people experience objectification, which further damages individuals’ well‐being, performance and social relationships (for a review, Baldissarri et al., 2022). For example, people suffering from objectification not only experience lower levels of authenticity and well‐being (Cheng et al., 2022), but also showed less prosocial behaviour and greater aggression towards others (Belmi & Schroeder, 2021; Poon et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more people acting as ‘objectifiers’ means more people experience objectification, which further damages individuals’ well‐being, performance and social relationships (for a review, Baldissarri et al., 2022). For example, people suffering from objectification not only experience lower levels of authenticity and well‐being (Cheng et al., 2022), but also showed less prosocial behaviour and greater aggression towards others (Belmi & Schroeder, 2021; Poon et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were required to complete a short scale that measures the extent to which one perceives oneself as a tool for goal achievement (i.e., self-instrumentality dimension). Previous research has already shown that people can use others as a tool or an instrument (e.g., Cheng et al, 2021; Gruenfeld et al, 2008; Teng et al, 2016; X. Wang & Krumhuber 2017), and this instrumentality can also be present in self-perception (e.g., Baldissarri et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the aim of this research was to investigate systematically whether awe can predict and shape the level of humanness attributed to oneself (i.e., self-humanity), and, if so, in which direction. This is a crucial question because the level of humanness perceived in oneself affects various outcomes, including task engagement (Baldissarri & Andrighetto, 2021), immoral behavior (Kouchaki et al, 2018), well-being (Cheng et al, 2022), and motivation to reach full potential (Wang, Chen, & Chen, 2022).…”
Section: Self-humanitymentioning
confidence: 99%